In vitro inhibitory activities of the extract of hibiscus sabdariffa l. (2013)
Literature is scanty on the interaction potential of Hibiscus sabdariffa L., plant extract with other drugs and the affected targets. This study was conducted to investigate the cytochrome P450 (CYP) isoforms that are inhibited by the extract of Hibiscus sabdariffa L. in vitro. The inhibition towards the major drug metabolizing CYP isoforms by the plant extract were estimated in human liver microsomal incubations, by monitoring the CYP-specific model reactions through previously validated N-in-one assay method. The ethanolic extract of Hibiscus sabdariffa showed inhibitory activities against nine selected CYP isoforms: CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1 and CYP3A4. The concentrations of the extract which produced 50% inhibition of the CYP isoforms ranged from 306 µg/ml to 1660 µg/ml, and the degree of inhibition based on the IC50 values for each CYP isoform was in the following order: CYP1A2 > CYP2C8 > CYP2D6 > CYP2B6 > CYP2E1 > CYP2C19 > CYP3A4 >> CYP2C9 >> CYP2A6. Ethanolic extract of Hibiscus sabdariffa caused inhibition of CYP isoforms in vitro. These observed inhibitions may not cause clinically significant herb-drug interactions; however, caution may need to be taken in co-administering the water extract of Hibiscus sabdariffa with other drugs until clinical studies are available to further clarify these findings.